The Wars of the Roses - Hicks, Michael, 1948- (Yale University Press, 2010)
"The Wars of the Roses (1455-85) were a major turning point in English history. But the underlying causes for the successive upheavals have been hotly contested by historians ever since. In this original and stimulating new synthesis, distinguished historian Michael Hicks examines the difficult economic, military, and financial crises and explains, for the first time, the real reasons why the Wars of the Roses began, why they kept recurring, and why, eventually, they ceased